An on-line monitoring system for wire electrical discharge turning process. (November 2015) - Yan, Mu-Tian; Hsieh, Pai-Hung
This article presents a new pulse discriminating system for process monitoring of wire electrical discharge turning. The pulse discriminating device, including a spark gap monitor and a digital signal processor card, has been developed to identify four major gap states classified as open circuit, normal spark, arc discharge and short circuit based on the characteristics of gap voltage waveform as well as compute ignition delay time for each open circuit and normal spark. By means of this system, the proportion of open circuit, normal spark, arc discharge and short circuit to total sparks and average ignition delay time within a time interval of 200 ms can be analyzed quantitatively during the wire electrical discharge turning process. It has been observed that thread cutting using wire electrical discharge turning exhibited more stable machining than cylindrical wire electrical discharge turning under a servo feed machining condition because servo feed control of the cylindrical wire electrical discharge turning process only focused on keeping forward sparking gap at a proper width, but it failed to respond to the variation of lateral gap width due to an independent motion of the rotary axis with respect to the translational axis. Experimental results also demonstrate that these pulse train data and average ignition delay time can substitute for average gap voltage as sensing parameters for on-line monitoring and control of the wire electrical discharge turning process.